2019
DOI: 10.1155/2019/7927083
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Etiology of Abnormally Large Gastric Folds: Menetrier’s Disease

Abstract: Menetrier’s disease (MD) is described as hypertrophied giant gastric folds causing hypoproteinemia due to protein losing gastropathy and is associated with higher risk of gastric adenocarcinoma. We present a case of a 58-year-old male who presented to our clinic with Melena and endoscopic work up showed enlarged gastric folds and erythematous mucosa in the antrum and three nonbleeding angioectasias in the duodenum. Mucosa biopsies were negative for H. pylori infection. He underwent polypectomy which showed fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Upper gastrointestinal bleeding has been reported as a rare manifestation of Ménétrier’s disease. The bleeding may present as hematemesis or, like in this case, as melena[ 10 , 11 ]. One patient developed deep vein thrombosis and received anticoagulation therapy, which led to gastrointestinal bleeding[ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Upper gastrointestinal bleeding has been reported as a rare manifestation of Ménétrier’s disease. The bleeding may present as hematemesis or, like in this case, as melena[ 10 , 11 ]. One patient developed deep vein thrombosis and received anticoagulation therapy, which led to gastrointestinal bleeding[ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…One study reported that H. pylori was present in 90% of Menetrier cases [ 4 ]. There is also a strong correlation with the overexpression of transforming growth factor-alpha (TGF-a), an epidermal growth factor receptor (EGFR) that is thought to play a major role in the proliferation of the gastric epithelium and gastric mucosal cells [ 5 ]. It is theorized that H. pylori plays a role in this overexpression.…”
Section: Discussionmentioning
confidence: 99%
“…The protein loss, specifically albumin, causes a state of fluid extravasation in peripheral tissues, leading to edema, most prominent in the lower extremities. Patients can also present with gastrointestinal bleeding [ 5 ]. There have been few reports of Menetrier presenting with intussusception, causing small bowel obstruction [ 1 , 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, he believed that the disease involved the stomach and the fundus of the stomach, and the antrum was preserved. The disease has a certain connection with gastric cancer[ 4 , 5 ]. With the continuous reports of cases, we have found that a few cases can involve the gastric antrum.…”
Section: Introductionmentioning
confidence: 99%